2021
DOI: 10.1590/0001-3765202120200233
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of chlorpyrifos, cypermethrin and glyphosate on the non-target organism Selenastrum capricornutum (Chlorophyta)

Abstract: The toxic effects of the insecticides chlorpyrifos and cypermethrin, and the herbicide glyphosate on the growth, biovolume and ultrastructure of the green microalgae Selenastrum capricornutum were evaluated. Concentrations between 9.37-150 mg L -1 of chlorpyrifos, 3.12-100 mg L -1 of cypermethrin and 4.7-60 mg L -1 of glyphosate were assayed along with a control culture. The assayed concentrations were prepared using commercial formulations. After 48 h all tested concentrations of the three pesticides reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…The toxicity of GBHs on algae species was investigated in several studies [ 115 , 116 , 117 ]. The toxicity values determined for Roundup Classic (corrected with glyphosate content) on P. subcapitata (72 h EC 50 values: 5.1 ± 1.3 mg/L) correlated well with some of the published 72 h EC 50 values (0.7–5.8 mg/L) for Roundup formulations [ 15 , 73 , 118 ]; however, they remain well below the values published in other studies (15.6–64.7 mg/L) [ 52 , 119 ]. In contrast to the 72 h EC 50 values demonstrated on the MSDS of the tested formulations for algal test organisms (72 h EC 50 values = 2.1 mg/L ( P. subcapitata , Roundup Classic) and 140 mg/L ( D. subspicatus , Medallon Premium) [ 97 , 98 ]), our toxicity values were significantly higher.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The toxicity of GBHs on algae species was investigated in several studies [ 115 , 116 , 117 ]. The toxicity values determined for Roundup Classic (corrected with glyphosate content) on P. subcapitata (72 h EC 50 values: 5.1 ± 1.3 mg/L) correlated well with some of the published 72 h EC 50 values (0.7–5.8 mg/L) for Roundup formulations [ 15 , 73 , 118 ]; however, they remain well below the values published in other studies (15.6–64.7 mg/L) [ 52 , 119 ]. In contrast to the 72 h EC 50 values demonstrated on the MSDS of the tested formulations for algal test organisms (72 h EC 50 values = 2.1 mg/L ( P. subcapitata , Roundup Classic) and 140 mg/L ( D. subspicatus , Medallon Premium) [ 97 , 98 ]), our toxicity values were significantly higher.…”
Section: Discussionsupporting
confidence: 83%
“…The toxic effects of glyphosate and its formulations have been studied in numerous aquatic organisms, such as various algae species [ 51 , 52 ], crustaceans (e.g., Daphnia magna ) [ 53 ], mollusks [ 54 ], fish [ 55 ], and amphibians [ 56 ]. Based on the results of ecotoxicological testing performed on a wide range of aquatic plant and animal organisms, the damage to different physiological and behavioral functions was demonstrated [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, this impact on electron transport was accompanied by a weaker ability to dissipate excess energy (Dio/RC) in the Arctic diatom, resulting in its greater sensitivity to chlorpyrifos. In addition, some authors have suggested that insecticides disturb the cell cycle of Selenastrum capricornutum since they observed the inhibition of cell-separation, resulting in the intracellular accumulation of macromolecules, which are responsible for increasing the biovolume in A-CN (Fernandez et al 2021, Rioboo et al 2002.…”
Section: Different Physiological Characteristics Between Arctic Micro...mentioning
confidence: 99%
“…Previous studies have been done on the toxicity of pesticides to evaluate the effects of chlorpyrifos individually on growth, chlorophyll contents, enzyme activities (Chen et al, 2016;Bhuvaneswari et al, 2018), and microalgal cell ultrastructure (Asselborn et al, 2015;Fernández et al, 2021). Meanwhile, mancozeb induces DNA damage and necrosis in HepG2 and A549 cell lines (Lori et al, 2021).…”
Section: Introductionmentioning
confidence: 99%